Depression in multiple system atrophy: Views on pathological, clinical and imaging aspects - Lv, Qiuyi; Pan, Yuxin; Chen, Xing; Wei, Jingpei; Wang, Wei; Zhang, Hua; Wan, Jifeng; Li, Shiqiang; Zhuang, Yan; Yang, Baolin; Ma, Dayong; Ren, Dawei; et al. (Frontiers in Psychiatry, 2022)
Multiple system atrophy (MSA) is a common atypical parkinsonism, characterized by a varying combination of autonomic, cerebellar, and pyramidal systems. It has been noticed that the patients with MSA can be accompanied by some neuropsychiatric disorders, in particular depression. However, there is limited understanding of MSA-related depression. To bridge existing gaps, we summarized research progress on this topic and provided a new perspective regarding pathological, clinical, and imaging aspects. Firstly, we synthesized corresponding studies in order to investigate the relationship between depression and MSA from a pathological perspective. And then, from a clinical perspective, we focused on the prevalence of depression in MS patients and the comparison with other populations. Furthermore, the associations between depression and some clinical characteristics, such as life quality and gender, have been reported. The available neuroimaging studies were too sparse to draw conclusions about the radiological aspect of depression in MSA patients but we still described them in the presence of paper. Finally, we discussed some limitations and shortcomings existing in the included studies, which call for more high-quality basic research and clinical research in this field.